Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1200/jop.2016.019372
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Palliative Care Services in Ambulatory Oncology: An Application of the Edmonton Symptom Assessment System

Abstract: PurposeResearch in palliative care demonstrates improvements in overall survival, quality of life, symptom management, and reductions in the cost of care. Despite the American Society of Clinical Oncology recommendation for early concurrent palliative care in patients with advanced cancer and high symptom burden, integrating palliative services is challenging. Our aims were to quantitatively describe the palliative referral rates and symptom burden in a South Texas cancer center and establish a palliative refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…The single QoL question has been validated and was found to be comparable to multi-item questionnaires [16]. It has been used extensively in the PC population with cancer [14,[17][18][19][20][21][22][23]. Based on extant literature and our communication with the PC team, there was mutual agreement that the ESAS-r with the global QoL question (ESAS-r + 1QoL) would be used for the assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The single QoL question has been validated and was found to be comparable to multi-item questionnaires [16]. It has been used extensively in the PC population with cancer [14,[17][18][19][20][21][22][23]. Based on extant literature and our communication with the PC team, there was mutual agreement that the ESAS-r with the global QoL question (ESAS-r + 1QoL) would be used for the assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of referrals to palliative care has been reported to improve considerably after the implementation of systematic evaluation with simple tools such as the Edmonton Symptom Assessment Tool. 17 This strategy may be useful in settings where palliative care services are limited and may lead to an optimization in the selection of symptomatic patients.…”
Section: Barriers To Early Supportive and Palliative Carementioning
confidence: 99%
“…The rate of referrals to subspecialty palliative care in cancer centers in the United States ranges from 8.5% to 46%. 17,18 Additionally, the utilization of other supportive care services among patients with advanced cancer varies according to the studied service, with reported referral rates of 15.1% to physical therapy, 25% to nutrition, and 29.7% to psychiatric/psychological counseling. 16 However, the World Health Organization estimates that only about 14% of patients in need of palliative care globally are able to access subspecialty palliative care.…”
Section: Supportive and Palliative Care Utilizationmentioning
confidence: 99%
“…20 In addition to its clinical significance, the ESAS has also been used as a trigger for referrals to specialized palliative care services. 6,21,22 Recently, a study found that patient exposure to the ESAS (measured by completing the ESAS at least once) was associated with improved survival in cancer patients. 23 While numerous studies have assessed the validity, clinical significance, and usability 7,12,13,16 of the ESAS, fewer studies have examined the patient experience surrounding the ESAS.…”
Section: Introductionmentioning
confidence: 99%